A institucionalidade da Extensão Universitária a partir do SIGAA: perspectiva dos docentes extensionistas da Universidade Federal da Paraíba - Falcão, Luiz Daniel Costa (2020)
The theme of University Extension is part of the idea of university functions, which is based on three pillars: teaching, research and extension, which must be equivalent and inseparable from each other for the university to perform its social role well. The university extension seeks to integrate itself with teaching and research in order to promote the interaction between university and society, as well as operationalize the theory-practice relationship in the training of different professionals. The Universidade Federal da Paraíba (UFPB), in line with the national scenario, has been working over the years to institutionalize the Extension, apprehended among other aspects in the systematization, registration and analysis of the extension activities carried out. The SIGAA extension module, implemented since 2017, is the current system for registering extension actions at UFPB, which has enabled a significant advance in the management of actions, however, as it is a system recently adopted, it has been the target of some complaints by users, which led to the following question: Is SIGAA satisfactory as a tool for recording extension actions developed at UFPB? To answer this question, the aim of this study was to assess the institutionality of university extension based on SIGAA from the perspective of extensionists professors from UFPB. To this end, a qualitative approach was used, from the perspective of exploratory and descriptive research, in which case study procedures are used; literature review, followed by a document analysis based on data made available by the extension module of SIGAA for the period from 2017 to 2019, and a field survey with the application of a semi-structured questionnaire to extension teachers and interviews with extension advisors of the institution . In the evaluated period, a positive evolution was observed in the UFPB extension production based on the reports generated by the SIGAA extension module. This module, in turn, showed good acceptability by the professors, the vast majority of the research participants considered the module implementation a great advance for registration of extension actions, however, they presented points where the system could be improved, along with suggestions for improvements. The present study carried out a historical contextualization of extension in Brazil and at UFPB; judiciously and participatively assessed the acceptability of the SIGAA extension module as a system for recording extension activities in this HEI; and invited the reader to reflect about the importance of an efficient registration for strengthening extension as academic and social practice. The data found may help the management sector to improve the system and thus the extension registration at UFPB. It is believed, therefore, that this research has contributed to the institutionalization of university extension based on the efficient registration of its practices.